Interaction of the Olfactory System of Rainbow Trout (Oncorhynchus mykiss) with Diltiazem. (28th October 2020) - Lari, Ebrahim; Burket, S. Rebekah; Steinkey, Dylan; Brooks, Bryan W.; Pyle, Greg G.
Abstract: Diltiazem is ubiquitously prescribed and has been reported in many effluents and freshwater bodies. Being a calcium channel blocker, diltiazem could disrupt the function of the sensory and central nervous systems. In the present study, using electro‐olfactography (EOG), we investigated the interaction of diltiazem with the olfactory sensory neurons (OSNs) of rainbow trout by looking into the detection threshold and effects of immediate (~5 min) and acute (24 h) exposure to diltiazem at 6.6, 66, and 660 µg/L. We also studied the accumulation of the drug in fish plasma and whole body. Brief exposure to diltiazem impaired the OSN response to a chemosensory stimulus in a concentration‐dependent manner at 6.6 µg/L and higher, whereas OSNs exposed for 24 h only displayed an impairment at 660 µg/L. Chemical analysis showed that the accumulation of diltiazem in fish plasma and body correlated with the EOG response because it was 10 times higher in the group that displayed a significant impairment (660 µg/L) compared to the other 2 groups (6.6, 66 µg/L). This correlation suggests that the impact of diltiazem on OSNs might partially be through the accumulated molecules in the fish bloodstream. Fish did not detect diltiazem as a sensory stimulus even at concentrations as high as 660 µg/L; thus, fish could potentially swim toward or fail to escape harmful concentrations of diltiazem. Environ Toxicol Chem 2022;41:554–550. © 2020 SETAC